Neurovascular Behçet's Disease Presenting with Cavernous Sinus Thrombosis: A Rare Case of Assumed Tolosa-Hunt-Like Syndrome - Chong Hyuk CHUNG,; Myeung Su LEE,; Changhoon LEE, (Archives of Rheumatology, 2020)
Behçet’s disease (BD) is a rare, chronic, auto-inflammatory disorder of unknown origin. Mucocutaneous lesions and pan-uveitis constitute the hallmark of BD. Additionally, vessels of all sizes and types are affected. In this article, we report a 53-year-old female patient diagnosed with neurovascular BD with diplopia, ipsilateral headache and ophthalmoplegia associated with cavernous sinus thrombosis, leading to Tolosa-Hunt-like syndrome. To our knowledge, this is the first report of a patient with complicated cavernous sinus thrombosis in BD.